(untitled) (Journal of Informatics and Mathematical Sciences, 2012)
A delay matrix T_d is derived and used along with the Chebyshev matrix of integration in a new algorithm for analysis and parameter identification of time-delay systems. The method reduces the problem to a set of algebraic equations. In addition, the Chebyshev wavelets are more successful in analyzing and identifying time-delay systems when compared with the other algorithms (polynomial series). The examples support this claim.